FalconSign: An Efficient and High-Throughput Hardware Architecture for Falcon Signature Generation - Yi Ouyang; Yihong Zhu; Wenping Zhu; Bohan Yang; Zirui Zhang; Hanning Wang; Qichao Tao; Min Zhu; Shaojun Wei; Leibo Liu (Transactions on Cryptographic Hardware and Embedded Systems)
Falcon is a lattice-based quantum-resistant digital signature scheme renowned for its high signature generation/verification speed and compact signature size. The scheme has been selected to be drafted in the third round of the post-quantum cryptography (PQC) standardization process due to its unique attributes and robust security features. Despite its strengths, there has been a lack of research on hardware acceleration, primarily due to its complex calculation flow and floating-point operations, which hinders its widespread adoption. To address this issue, we propose FalconSign, a high-performance, configurable crypto-processor designed to accelerate Falcon signature generation on FPGA/ASIC through algorithmhardware co-design. Our approach involves a new scheduling flow and architecture for Fast-Fourier Sampling to enhance computing unit reuse and reduce processing time. Additionally, we introduce several optimized modules, including configurable randomness generation units, parallel floating-point processing units, and an optimized SamplerZ module, to improve execution efficiency. Furthermore, this paper presents a finely optimized hardware accelerator for the Falcon scheme. Our FPGA implementation results demonstrate a throughput improvement of approximately 5.1 x compared to state-of-the-art designs, with 2.8x/4.5x/4.2x/3.2x fewer in the area (LUTs/FFs/DSPs/BRAMs)-time product, for NIST security level V. The crypto-processor occupies an area of 0.71 mm2 and achieves 5.2k OPS at throughput on the TSMC 28nm process for NIST security level I.